Potential of phenylalanine-, tryptophan-, and tyrosine-MOF-5 composites for selective carbon dioxide and methane adsorption - Moyosore, Abdullahi; Ahmad, Haslina; Muhammad Latif, Muhammad Alif; Borzehandani, Mostafa Yousefzadeh; AbdulRahman, Mohd Basyaruddin; Abdelmalek, Emilia (John Wiley and Sons Inc, 2024)
Metal-organic frameworks (MOFs) have emerged as versatile materials with exceptional properties, including high porosities, large surface areas, and remarkable stabilities, making them attractive for various applications. MOF-5 stands out for its thermal stability and surface area, making it promising for diverse applications, including drug delivery and gas adsorption. This study explores the potential of amino acid MOF (AA-MOF) composites, integrating phenylalanine, tryptophan, and tyrosine, for selective CO2 and CH4 adsorption using grand canonical Monte Carlo (GCMC) simulations. The impact of amino acid composition and spatial arrangement within MOF-5 on selective CO2 and CH4 adsorption performance have been investigated. The results indicate that tryptophan-MOF-5 exhibits the highest CO2 uptake due to the interaction between CO2 and tryptophan, while phenylalanine-MOF-5 demonstrated the lowest affinity for gas adsorption. Radial distribution function (RDF) analysis reveals distinct gas distribution patterns within the composites, with tryptophan playing a dominant role in gas adsorption. Additionally, analysis of total energy, enthalpy of adsorption, and Henry's coefficient provide insights into the thermodynamic aspects of gas adsorption onto AA-MOF composites. This study enhances the understanding of the fundamental mechanisms underlying CO2 and CH4 selective adsorption in amino acid MOF composites, facilitating the development of efficient gas separation technologies.